PENGARUH KOMUNIKASI, KOMITMEN ORGANISASI SECARA VIRTUAL DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN STUDI KASUS PADA RSU PKU MUHAMMADIYAH DELANGGU - Muhammad Rizal Nur Wakhid; Ahmad Mardalis (LP2M Universitas Bina Bangsa, 2024)
This research is based on complaints that occurred during the offline and online transition period. By aiming to determine the effect of job satisfaction, communication and organizational commitment virtually on employee performance. The study used quantitative research methods with the distribution of respondent samples through questionnaires totaling 80 data and employees of RSU PKU Muhammadiyah Delanggu as the sample subjects tested. Sampling in this study used purposive sampling method. With the help of SmartPLS data analysis application as a sample test tool, using data analysis testing such as outer model, inner model. The findings of this study state that there is an influence on job satisfaction on employee performance, and there is an influence of communication on employee performance, and there is an influence of organizational commitment virtually on employee performance